Assessment of the Relationship Between Polycystic Ovary Syndrome and Insulin Resistance in Adolescent Females - Sajida Razzaq, Sofia Manzoor, Sadia Dilawar, Shazia Saaqib, Mahpara Shaukat, Azka Tariq, Mahwish Ashraf, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders among adolescent females, characterized by hyperandrogenism, menstrual irregularity, and polycystic ovarian morphology. Objective: To assess the relationship between polycystic ovary syndrome and insulin resistance among adolescent females. Methodology: This cross-sectional multicentered study was conducted at Sir Ganga Ram Hospital, Lahore and Sahiwal Teaching Hospital, Sahiwal from December 2022 to June 2023. 255 adolescent females aged 13–19 years diagnosed with PCOS according to the modified Rotterdam criteria. Data were collected through detailed history, physical examination, and biochemical analysis. Fasting glucose and fasting insulin levels were measured, and insulin resistance was calculated using the Homeostatic Model Assessment for Insulin Resistance (HOMA-IR). Results: The mean age of participants was 16.8 ± 1.7 years, and the mean BMI was 27.6 ± 4.3 kg/m². Menstrual irregularity (85.1%) and acne (71.0%) were the most frequent clinical findings. The mean fasting glucose was 92.8 ± 9.4 mg/dL, fasting insulin was 17.5 ± 6.2 µU/mL, and mean HOMA-IR was 3.9 ± 1.4. Insulin resistance (HOMA-IR > 2.5) was present in 67.8% of participants. A significant association was observed between insulin resistance and BMI (p < 0.001), acanthosis nigricans (p < 0.001), menstrual irregularity (p = 0.002), and elevated testosterone levels (p = 0.004). A positive correlation was also noted between HOMA-IR and BMI (r = 0.54) as well as fasting insulin (r = 0.72). Conclusion: It is concluded that insulin resistance is highly prevalent among adolescent females with PCOS and is significantly associated with both metabolic and reproductive abnormalities. Since IR can occur even in non-obese individuals, routine screening should be performed in all adolescents with PCOS. Keywords: Polycystic ovary syndrome, Insulin resistance, Adolescents, HOMA-IR, Hyperandrogenism.